Variasi Komposisi Bentonit pada Cetakan Pasir Blok Silinder Mesin Pemotong Rumput - Sofian Wijayanto; Sunyoto Sunyoto (Jurnal Dinamika Vokasional Teknik Mesin, 2019)
Purpose of this research is to find out how the influence of variation of bentonite composition on the sand mold to casting defect, hardness, and microstructure. Variations of bentonite composition used were 0%, 8%, and 16%. The data of the research were analyzed directly using graphs and micro photographs which were then drawn conclusions from the results of the study. Needle-hole defects are found in all variations of bentonite composition. The porosity defect was found only in the variation of 0% and 16% bentonite compositions. The highest hardness value was obtained from the 8% bentonite composition variation is 84.26 VHN and the lowest hardness value was obtained from 0% VHN bentonite composition variation is 68.02 VHN. The best microstructure is indicated by the variation of 8% bentonite composition as evidenced by the formation of Al and Si elements that are evenly distributed and closer to the grain.Tujuan penelitian ini adalah untuk mengetahui bagaimana pengaruh variasi komposisi bentonit pada cetakan pasir terhadap cacat coran, kekerasan dan struktur mikro. Variasi komposisi bentonit yang digunakan adalah 0%, 8% dan 16%. Data hasil penelitian dianalisis secara langsung menggunakan grafik dan foto mikro yang kemudian  ditarik  kesimpulan  dari  hasil  penelitian  tersebut.  Cacat lubang jarum ditemukan di semua variasi komposisi bentonit. Sedangkan cacat porositas hanya ditemukan pada variasi komposisi bentonit 0% dan 16. nilai kekerasan tertinggi diperoleh dari variasi komposisi bentonit 8% sebesar 84.26 VHN dan nilai kekerasan terendah diperoleh dari variasi komposisi bentonit 0% sebesar 68.02 VHN. Struktur mikro terbaik ditunjukkan oleh variasi komposisi bentonit 8% dibuktikan dengan pembentukan unsur Al dan Si yang merata dan lebih merapat letak antar butirnya.